CADANGAN PROSPEKTIF LAST SURVIVOR DENGAN ASUMSI GOMPERTZ - ', Ghufron; ', Hasriati; ', Bustami (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses prospective reserve of premium last survivor endowment insurance. Last survivor endowment insurance is a type of life insurance of two persons  whose ages are